2005
DOI: 10.1152/ajpgi.00001.2005
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of apoptosis in enterocytes by blockade of potassium channels

Abstract: Apoptosis plays an important role in maintaining the balance between proliferation and cell loss in the intestinal epithelium. Apoptosis rates may increase in intestinal pathologies such as inflammatory bowel disease and necrotizing enterocolitis, suggesting pharmacological prevention of apoptosis as a therapy for these conditions. Here, we explore the feasibility of this approach using the rat epithelial cell line IEC-6 as a model. On the basis of the known role of K+ efflux in apoptosis in various cell types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…It has been previously demonstrated that K ϩ efflux is one of the earliest events of the apoptotic process in metazoan cells and is presumed to be necessary for activation of the biochemical apoptotic pathways (4,8,15,21,41,48). However, a similar role for the intracytoplasmic loss of potassium ions has not been reported in fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously demonstrated that K ϩ efflux is one of the earliest events of the apoptotic process in metazoan cells and is presumed to be necessary for activation of the biochemical apoptotic pathways (4,8,15,21,41,48). However, a similar role for the intracytoplasmic loss of potassium ions has not been reported in fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the mitochondrial transmembrane potential (⌬⌿ m ) have been considered as a hallmark of apoptosis (28). To determine the ability of rhLf to induce mitochondrial depolarization, the ⌬⌿ m was quantified by Rh-123 uptake, using suspensions of cells treated for different periods of time with rhLf (15,30,60,120, and 180 min). As Fig.…”
Section: Vol 52 2008 Lactoferrin Induces Apoptosis In Yeast 4083mentioning
confidence: 99%
“…The two phases of AVD are accomplished by the same mechanism that includes outward fluxes of K 1 and Cl -moving across specific channels and a decrease in osmolyte intracellular concentration and water outflow resulting in AVD (Kondratskyi et al, 2015). It has yet to be determined whether this decrease in cell volume is a passive factor or an active signal in the induction of apoptosis, but evidence does exist that points to an explicit role for volume decrease in the apoptotic process; blockade of the main osmolyte pathways that reduce AVD impairs the progression of apoptosis (Yu and Choi, 2000;Grishin et al, 2005).…”
Section: Channels Involved In Volume Changes In Necrotic and Apoptotimentioning
confidence: 99%
“…In rat epithelial cells, potassium channels blockers such as TEA, 4-AP, stromatoxin, chromanol 293B, and 48F10 were shown to prevent AVD and apoptosis [28]. Early studies on neuronal cell death also demonstrated the importance of potassium as a key regulator of apoptosis [29][30][31].…”
Section: Potassium As a Key Player In The Regulation Of Apoptosismentioning
confidence: 99%